2019
DOI: 10.18087/cardio.2600
|View full text |Cite
|
Sign up to set email alerts
|

Blood lipids and angina pectoris (by epidemiological cardiological Rose questionnaire) in the population of 25-45 years of Novosibirsk

Abstract: The aim of the study was to investigate the prevalence of angina pectoris (AP) according to the standardized epidemiological questionnaire of Rose in the population of 25–45 years of Novosibirsk and to identify its association with some lipid and non-lipid risk factors for coronary heart disease (CHD). Material and methods. Cross-sectional survey of the population aged 25–45 in Novosibirsk was carried out. The study included 1439 people (656 men and 783 women). Within the framework of the complex survey progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This study identified an association of grade I angina with self-declared black and mixed race/color and with living in rural areas, reinforcing the relationship of social characteristics and poorer access to health promotion and preventive measures 16 . Among the study's limitations, we highlight a strong association between "positive" responses to the questionnaire and the presence of common mental disorders 4,19,20 . Thus, the positive response could be due to somatization or increased sensitivity to pain in depressed or anxious people, and not exactly to a manifestation of coronary ischemia 4,19 .…”
Section: Discussionmentioning
confidence: 86%
“…This study identified an association of grade I angina with self-declared black and mixed race/color and with living in rural areas, reinforcing the relationship of social characteristics and poorer access to health promotion and preventive measures 16 . Among the study's limitations, we highlight a strong association between "positive" responses to the questionnaire and the presence of common mental disorders 4,19,20 . Thus, the positive response could be due to somatization or increased sensitivity to pain in depressed or anxious people, and not exactly to a manifestation of coronary ischemia 4,19 .…”
Section: Discussionmentioning
confidence: 86%
“…The duration of diabetes from 6 to 10 years was recorded in 35 (12.72%) patients, from 10 to 15 years -in 153 (55.63%) patients, more than 15 years -in 87 (31.63%) patients. In the studied patients, the Rose [4], [5], questionnaire recommended by the WHO for the detection of exertional angina, anamnestic data on hospitalization with angina pectoris or myocardial in fact, data of daily monitoring of ECG, and EchoCG was used for screening. The average duration of IHD in patients was 10.7 ± 1.47 years.…”
Section: Methodsmentioning
confidence: 99%